Doping of Organic Semiconductors: Impact of Dopant Strength and Electronic Coupling1. Issue 30 (19th June 2013) - Méndez, Henry; Heimel, Georg; Opitz, Andreas; Sauer, Katrein; Barkowski, Patrick; Oehzelt, Martin; Soeda, Junshi; Okamoto, Toshihiro; Takeya, Jun; Arlin, Jean‐Baptiste; Balandier, Jean‐Yves; Geerts, Yves; et al.
<x xml:space="preserve">Abstract</x> Molecular doping: The standard model for molecular p‐doping of organic semiconductors (OSCs) assumes integer charge transfer between OSC and dopant. This is in contrast to an alternative model based on intermolecular complex formation instead. By systematically varying the acceptor strength it was possible to discriminate the two models. The latter is clearly favored, suggesting strategies for the chemical design of more efficient molecular dopants.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>